The Play in the System : The Art of Parasitical Resistance - Fisher, Anna Watkins (Book collections on Project MUSE., 2020)
"In THE PLAY IN THE SYSTEM Anna Watkins Fisher asks what kind of room for maneuver remains in a system from which there appears to be no way out. Arguing that traditional leftist modes of opposition and refusal, which presuppose an autonomous or emancipatory subject, have proven ill-adapted to today's murky political terrain, Fisher focuses on new media artists and activists who embrace what she calls parasitism. Fisher defines parasitism as a tactical mode through which precarious subjects (at least, those with enough capital to get a foot in the door) can leverage the minor advantages of appearing familiar and non-threatening to those who hold power over them. Using powerful entities' pretense of benevolence to gain access, parasitical artists are then (like Trojan horses) able to disrupt the smooth functioning of these entities. In acknowledging our inevitable entanglement in the oppressive systems and institutions we most need to resist, Fisher's parasites create space to relinquish investments in purity and weaponize complicity. The first half of the book focuses on works that target large corporations-major "hosts"-whose appropriation of transparency and facilitation masks their proprietary gatekeeping and monetization of public goods. But Fisher's book does not only laud parasitical activists like the collective Ubermorgen, whose Amazon Noir project exploited Amazon's "search inside the book" feature to produce open access versions of over 3,000 books. The book's second half considers what happens when the boundary between host and parasite becomes blurrier, grappling with the more messy contradictions posed by parasitical works that share a genealogy with feminist performance art. Here, works like Chris Kraus' I Love Dick and Sophie Calle's Take Care of Yourself play on the intimacy of the author/artist's relationship with a privileged man. In the book's coda, Fisher considers her own parasitic relationship with feminist performance artist Roisin Byrne, reflecting on the shifting parasitical relationships between artists and critics. This book will be of interest to readers in media studies, especially new media studies, as well as those in contemporary art and performance studies, feminist studies, political and social theory, and cultural studies, as well as those interested in neoliberalism and anti-capitalist activism"--